Empire of emptiness : Buddhist art and political authority in Qing China - Berger, Patricia Ann (University of Hawaii Press, 2003)
Imperial Manchu support and patronage of Buddhism, particularly in Mongolia and Tibet, has often been dismissed as cynical political manipulation. Empire of Emptiness questions this generalization by taking a fresh look at the huge outpouring of Buddhist painting, sculpture, and decorative arts Qing court artists produced for distribution throughout the empire. It examines some of the Buddhist underpinnings of the Qing view of rulership and shows just how central images were in the carefully reasoned rhetoric the court directed toward its Buddhist allies in inner Asia. The multilingual, culturally fluid Qing emperors put an extraordinary range of visual styles into practice--Chinese, Tibetan, Nepalese, and even the European Baroque brought to the court by Jesuit artists. Their pictorial, sculptural, and architectural projects escape easy analysis and raise questions about the difference between verbal and pictorial description, the ways in which overt and covert meaning could be embedded in images through juxtaposition and collage, and the collection and criticism of paintings and calligraphy that were intended as supports for practice and not initially as works of art.